Re-examining intercultural research and relations in the COVID pandemic. (January 2021) - Kulich, Steve J.; Komisarof, Adam; Smith, L. Ripley; Cushner, Kenneth
Abstract: The authors provide an urgent call for cross- and intercultural scholars to re-examine many of the related themes and classic or contemporary study areas of "intercultural communication" and "intercultural relations" in light of the impacts that the novel coronal (COVID-19) pandemic is having on human interaction both across and within our social-cultural contexts. As scholars focusing on intercultural communications/relations, education, management, psychology, and social issues, the global COVID-19 pandemic has revealed a range of intercultural problems or issues that need to be researched to better understand related aspects of human suffering, social disruption, and economic inequalities. New research projects/papers need to address how these impact key intercultural theme/topic areas like cultural attributions/expectations, values/beliefs, identities, perceptions/stereotypes/prejudice, language/speech codes, cultural systems/patterns, acculturation/adaptation, intercultural effectiveness/sensitivity/competence, and conflict (Kulich et al., 2020, Table 3.7). Some research areas and applications potentially affected by COVID are highlighted, including our sense of national/international identity and cooperation, our mediated or actual social networks, our ways of framing or carrying out intercultural or cross-cultural cooperation, new issues emerging in inter-group contact, how we apply cross-cultural taxonomies or dimensions to analyze data, and how these ultimately affect our relationships with each other across all levels of culture (from dyads, to groups, sub- or co-cultures) or express and affirm interculturality at such times. Each area is highlighted by calls for specific types of intercultural research to address these challenges and opportunities.